2021
DOI: 10.1186/s12877-021-02347-y
|View full text |Cite
|
Sign up to set email alerts
|

Is multimorbidity associated with risk of elder abuse? Findings from the AHSETS study

Abstract: Background With an increasing number of older adults in low- and middle-income countries (LMIC), the burden of multimorbidity and functional dependence is on the rise. At the same time, a higher prevalence of elder abuse is observed in these populations. There is scarce evidence on the interplay between elder abuse and multimorbidity with no reports from LMIC settings yet. Present study examined the association of multimorbidity with the risk of elder abuse and its correlates in a rural elderly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
8
0
2
Order By: Relevance
“…Recent studies have revealed that there exist significant associations between obesity [ 28 ] and loneliness [ 29 ] accompanied by multimorbidity in India. Another recent study has investigated in Odisha that multimorbidity increases the odds of older adults' abuse [ 30 ]. There are very few studies on multimorbidity prevalence and its associated risk factors among older adults in India.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that there exist significant associations between obesity [ 28 ] and loneliness [ 29 ] accompanied by multimorbidity in India. Another recent study has investigated in Odisha that multimorbidity increases the odds of older adults' abuse [ 30 ]. There are very few studies on multimorbidity prevalence and its associated risk factors among older adults in India.…”
Section: Introductionmentioning
confidence: 99%
“…We observed 60.5% (n=23) of the included studies were based on primary data 5 , 17 , 19 , 20 , 22 , 25 - 29 , 32 - 35 , 37 , 39 - 43 , 45 - 48 whereas 39.5% were from secondary data analysis of nationally representative samples such as Longitudinal Ageing Study in India (LASI) wave-0 (n=1), 18 Study on Global Ageing and Adult Health (SAGE) wave-0 15 (n=1), SAGE wave-1 16 , 21 , 24 , 36 , 44 (n=5), LASI wave-1 32 , 35 (n=2), Building Knowledge Base on Population Aging in India (BKPAI) 38 (n=1), India Human Development Survey (IHDS-II) 31 (n=1) and -United Nations Population Fund (UNFDPA) 23 (n=1). Fifteen studies were from Odisha 5 , 17 , 19 , 25 , 26 , 28 , 32 - 34 , 39 , 40 , 42 , 45 , 47 , 48 ; 12 studies 16 , 18 , 21 , 23 , 24 ,…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies were from Odisha 5 , 17 , 19 , 25 , 26 , 28 , 32 - 34 , 39 , 40 , 42 , 45 , 47 , 48 ; 12 studies 16 , 18 , 21 , 23 , 24 , 30 , 31 , 36 , 38 , 44 , 46 , 49 represented pan India and eight studies were from other states of India. 20 , 22 , 27 , 29 , 35 , 37 , 41 , 43 Eleven studies 5 , 19 , 25 , 26 , 28 , 32 , 33 , 34 , 39 , 43 , 47 were conducted in hospital/primary care (study conducted among patients attending hospitals/primary care) setting while 24 were from the community based set up (data collected by visiting household through face to face interviews) 16 - 18 , 20 ...…”
Section: Resultsmentioning
confidence: 99%
“…In this study, some variables and types of abuse were found to be significantly related. In the studies conducted in the literature, education level, 31,32 employment status, 14 health perception, 33 presence of psychiatric illness, 12,34 dependency in activities of daily living, 30,34,35 and low mental status 30,34 were among the factors associated with abuse.…”
Section: Discussionmentioning
confidence: 99%